АКСІАЛЬНІ МАГНІТНІ СИЛИ ТОРЦЕВОГО ДУГОСТАТОРНОГО ДВИГУНА З ДИСКОВИМ БІМЕТАЛЕВИМ РОТОРОМ - Карлов , О.М.; Кондратенко , І.П.; Крищук , Р.С.; Ращепкін , А.П. (Інститут електродинаміки Національної академії наук України, 2018)
The analytical method for calculating the axial magnetic forces that act on the rotor and on the stators of the arc-stator induction motor with a bimetallic disk rotor is developed. In the method the Maxwell tensor is used. The method uses the previously developed analytical calculation of the averaged over time complex value of the axial component of the electromagnetic induction in the gap between the stators. The method works both for the given complex values of the phase currents of the stators, and for the given complex phase voltages. Phase windings of stators are connected to the electrical network in series. The value of the axial forces acting on the disk rotor, and for each stator separately is determined for the gearless motor of the ball mills. The analytical method takes into account the three-dimensional induction distribution in the gap between the stators, the effect of the current displacement in the disk rotor, the asymmetrical position of the rotor in the gap, the mutual inductance of the phases of the two stators. References 7, figures 6, tables 2.